(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2009)
During the past few years (2002-2007), Peruvian exportation have had an excellent performance, not only the deficit of the commercial balance has been reversed, but also the positive balance has been growing in a sustainable way. Nevertheless, not the only the exporting enterprises have grown, but the Peruvian multinational enterprises have also developed. The MNE differ from the exporting enterprises not only by working at destination, but designing and managing different strategies related on the foreign direct investment (FDI) and counting on the other attributes that allows it to compete directly with the local enterprises. The object of the present article is to relate the FDI theory and the MNE with the Peruvian MNE, to explore on a theoretical basis the acting of Peruvian MNE and to what extent the expected results of the current theories on this point are fulfilled.